Indonesia Analisis Implementasi Green Banking Pada Perbankan Syariah (Studi Kasus Bank Muamalat KCP Payakumbuh) - Doni Iskandar; Iiz Izmuddin; Ali Rahman; Himmatul Khairi (Program Studi Ekonomi Islam - UIN Sjech M. Djamil Djambek Bukttinggi, 2025)
This research is based on the increasing environmental issues that encourage banks to transform their behavior and activities known as green banking. The concept of green banking is banking that emphasizes the implementation of sustainability in operational activities. Thus, banks strive to implement environmentally friendly practices by reducing the carbon footprint generated from banking operational activities. This study aims to analyze the implementation of the green banking concept in Islamic banking with a case study at Bank Muamalat KCP Payakumbuh. The research method used is descriptive qualitative with a field study approach, through direct interviews with parties at Bank Muamalat KCP Payakumbuh, and documentation. Data analysis techniques in this study are data collection, data reduction, data presentation, and drawing conclusions/verification. The results of the study indicate that Bank Muamalat KCP Payakumbuh has implemented green banking in stages based on research indicators, namely green banking indicators, namely Carbon Emissions, Green Building, Paperless, Reuse/Recycle/Refurbish Green Rewards And Green Investment. The implementation of environmentally friendly practices provides operational efficiency achieved through the implementation of green banking, helping banks reduce costs and increase work efficiency. The use of technology also plays a role in accelerating service processes and increasing customer satisfaction.